2020
DOI: 10.5817/cp2020-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Facebook intensity, social network support, stability and satisfaction in long-distance and geographically-close romantic relationships: A test of a mediation model

Abstract: The impetus for this study is the proposition that social network sites (SNSs), like Facebook, can be beneficial for romantic relationships via network support functions. This study investigated a model which proposes that the use of Facebook predicts relationship support from Facebook connections, and this, in turn, predicts relationship stability and satisfaction in romantic relationships. This mediation model was tested on data gathered via an online survey among individuals who use Facebook, who are in lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Similarly, perceptions of network helpfulness positively contribute to intimacy levels in couples (Knobloch & Donovan-Kicken, 2006). Lastly, increased online support from Facebook friends is positively linked to both relationship stability and satisfaction in long distance relationships (Billedo et al, 2020).…”
Section: The So Cial Ne T Work a S An Ind I C Ator Of Commitmentmentioning
confidence: 94%
“…Similarly, perceptions of network helpfulness positively contribute to intimacy levels in couples (Knobloch & Donovan-Kicken, 2006). Lastly, increased online support from Facebook friends is positively linked to both relationship stability and satisfaction in long distance relationships (Billedo et al, 2020).…”
Section: The So Cial Ne T Work a S An Ind I C Ator Of Commitmentmentioning
confidence: 94%
“…For instance, in some studies, Facebook use was associated with conflict (Clayton et al., 2013) and jealousy (Muise et al., 2009; Utz & Beukeboom, 2011), whereas other studies found that high Facebook use was associated with relationship satisfaction (Billedo et al., 2020; Saslow et al., 2013). One explanation for the lack of consistency among these related studies may be due, in part, to the trouble of identifying the many different social functions on SNSs (e.g., timeline scrolling, network messaging, partner surveillance, checking upcoming events; Billedo et al., 2015; Billedo et al., 2020; Frampton & Fox, 2018; Muise et al., 2014; Utz & Beukeboom, 2011). Thus, this study uses an active SNS measure in an attempt to include the broadest range of possible SNS activities rather than the variety of individual activities that can occur on SNSs.…”
Section: Snss’ Associations With and Effects On Romantic Relationship...mentioning
confidence: 99%
“…Indeed, the role of communication technologies in romantic relationships has increasingly altered the dynamic of romantic relationships to be predominantly accessed online (Alhabash & Ma, 2017;Clayton et al, 2013;Clayton, 2014;Fox & Moreland, 2015;Frampton & Fox, 2018;Utz, 2022;Yacoub et al, 2018). As a result, many studies have been conducted to investigate the complex interactions 2 DELLE, CLAYTON, JORDAN JACKSON, AND LEE between SNS use and romantic relationships (Billedo et al, 2020;González-Rivera & Hernández-Gato, 2019;Elphinston & Noller, 2011;Frampton & Fox, 2018). Although SNSs may be helpful to keep in touch with family and friends, there is a growing body of research showing that increased SNS use can be detrimental to romantic relationships (for a recent review, see Utz, 2022).…”
Section: Sns Usage and Associations With Romantic Relationship Stressmentioning
confidence: 99%
See 2 more Smart Citations